Enabling well-being and epistemological access through an authentic assessment intervention: A case study of a higher education programme - Maniram, R.; Maistry, S.M. (South African Journal of Higher Education, 2018)
The South African higher education context presents with multiple challenges. One such challenge is the ability of institutions to effectively respond to the academic needs of the students that enter university. While there are several instances of programme development that attempt to address the academic well-being of students, the pedagogic strategies of many programmes are often not well grounded in sound educational theory. In this paper, we report on a study that examined student experiences of an academic programme that is informed by the concepts ‘authentic assessment’ and ‘epistemological access. The methodological approach was guided by the tenets of Interactive Qualitative Analysis (IQA), (Northcutt and McCoy, 2004). A purposive sample of Hospitality Financial Management students at a university of technology was drawn. Key data generation instruments included individual and focus group interviews, online chats and online reflective journals. One compelling finding which we take up in this paper is the power of student collaboration as a powerful enabling mechanism for epistemic access.